Upaya Hukum Terhadap Debitur Pada Layanan Pinjaman Uang Berbasis Finansial Teknologi - Citra Citra (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
This study's objective is to investigate the legal remedies taken against debtors of technology-based financial lending services and how to avoid problems with technology-based money loan services. This research is normative legal research undertaken by reviewing and analyzing literature and statutory books. According to the findings of the research, legal remedies against debtors in peer-to-peer lending services are governed by Law No. 11 of 2008 regarding Information and Electronic Transactions. Law No. 21 of 2011 pertaining to the Financial Services Authority, Government Regulation No. 82 of 2012 pertaining to the Implementation of Electronic Systems and Transactions, Regulation of the Financial Services Authority No. 1/POJK.07/2013 of 2013 pertaining to Consumer Protection in the Financial Services Sector, Regulation of the Financial Services Authority No. 77/POJK.01/2016 Year 2016 pertaining to Information Technology-Based Lending and Borrowing Services, Minimal Capital Requirements, and Minimal Capital Requi Legal Efforts, Debtors, Money Loan Services, and Financial Technology are keywords.